Ethics and responsibilities of open access. Lessons learned from the Wikipedia project of the Atikamekw First Nation - Nastasia Herold; Thérèse Ottawa (2020)
With 97,9%, in Canada, the Atikamekw First Nation has the highest percentage of people who speak their native language (Atikamekw) at home. The Atikamekw live in Quebec and have a population of 8,000 people in three communities. Despite the vitality of the Atikamekw language, francization and language change are processes noticed by all living generations of the Atikamekw. Communication takes place more and more often digitally, and this in written language rather than orally. Atikamekw has a standardized orthography since 1994 and is taught in Manawan’s primary school as a first language and as medium of alphabetization. However, the Internet contained no written text in the Atikamekw language, the Atikamekw used the Internet mainly in French. This is why a school project at Manawan’s secondary school was initiated in 2013 in order to create a Wikipedia site in the Atikamekw language. Many lessons have been learned during the collaboration of academics, teachers, pupils, local language experts and other local voluntary contributors. The lessons we would like to focus on in this presentation are the lessons learned when implementing cultural knowledge to an open access platform. We will give four examples which show that the Atikamekw made sure that the knowledge was published respecting their own principles, beliefs and tradition. These four examples and the development of the project show how it is important that the community itself dictates rules that have to be respected when publishing their knowledge under open access. Finally we will answer Rehbein’s and Thies’ (2017: 355) question as a schema for questions of responsibilities and ethics of a specific project: Who (1) is responsible for what (2) to whom (3) before which instance (4) according to which standards (5)? References Rehbein, Malte / Thies, Christian (2017): “Ethik”, in: Jannidis, Fotis / Kohle, Hubertus / Rehbein, Malte (eds.): Digital Humanities. Eine Einführung. Stuttgart: J.B. Metzler 353- 357.